Integrating Literacy and Science in Biology: Teaching and Learning Impacts of Reading Apprenticeship Professional Development - Greenleaf, Cynthia L.; Litman, Cindy; Hanson, Thomas L.; Rosen, Rachel; Boscardin, Christy K.; Herman, Joan; Schneider, Steven A.; Madden, Sarah; Jones, Barbara (1998)
This study examined the effects of professional development integrating academic literacy and biology instruction on science teachers? instructional practices and students? achievement in science and literacy. The intervention consisted of 10 days of professional development in Reading Apprenticeship, an instructional framework integrating metacognitive inquiry routines into subject-area instruction to make explicit the tacit reasoning processes, problem-solving strategies, and textual features that shape literacy practices in academic disciplines. The study utilized a group-randomized, experimental design and multiple measures of teacher implementation and student learning and targeted groups historically unrepresented in the sciences. Hierarchical linear modeling procedures were used to estimate program impacts. Intervention teachers demonstrated increased support for science literacy learning and use of metacognitive inquiry routines, reading comprehension instruction, and collaborative learning structures compared to controls. Students in treatment classrooms performed better than controls on state standardized assessments in English language arts, reading comprehension, and biology.
Keywords: STEM; Professional Development; Reading comprehension; academic literacy; science literacy; disciplinary literacy